2018
DOI: 10.1073/pnas.1803130115
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70–Bag3 complex is a hub for proteotoxicity-induced signaling that controls protein aggregation

Abstract: Protein abnormalities in cells are the cause of major pathologies, and a number of adaptive responses have evolved to relieve the toxicity of misfolded polypeptides. To trigger these responses, cells must detect the buildup of aberrant proteins which often associate with proteasome failure, but the sensing mechanism is poorly understood. Here we demonstrate that this mechanism involves the heat shock protein 70-Bcl-2-associated athanogene 3 (Hsp70-Bag3) complex, which upon proteasome suppression responds to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 35 publications
0
68
1
Order By: Relevance
“…The depletion of SYNPO2 releases BAG3 from its autophagic roles and upregulates YAP/TAZ-mediated transcription [466]. It was recently reported that the BAG3-HSPA complex is critical in the LATS1/2-mediated phosphorylation of YAP, which is indicative of Hippo pathway activation [487].…”
Section: Regulation Of Expression By Bag3mentioning
confidence: 99%
“…The depletion of SYNPO2 releases BAG3 from its autophagic roles and upregulates YAP/TAZ-mediated transcription [466]. It was recently reported that the BAG3-HSPA complex is critical in the LATS1/2-mediated phosphorylation of YAP, which is indicative of Hippo pathway activation [487].…”
Section: Regulation Of Expression By Bag3mentioning
confidence: 99%
“…Moreover, BAG3 is recruited to stress granules via its interactions with HSPB8 where the BAG3-HSP8-HSP70 complex plays a key role in ensuring stress granule functionality (77). Disturbing the dynamic balance of the HSP27-BAG3 interaction might therefore affect a wider chaperone network and contribute to destabilization of proteostasis (78). Notably, mutations in the BAG3 IPV motifs also contribute to human disease: a Pro-to-Leu mutation is implicated in myofibrillar myopathy (34, 75, 79) and another Pro-to-Ser mutation is implicated in CMT disease (80).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the aggresomes are not formed in response to an overload of ubiquitinylated proteins. Whether the aggregation of BAG3 itself is the underlying cue to form aggresomes remains unclear since BAG3 was also shown to regulate aggresome formation through the Hippo pathway (Meriin et al 2018). So aberrant activation of the Hippo pathway may also explain the formation of aggresomes.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the BAG-domain is known to mediate the interaction with Hsp70/Hsc70 or Bcl2 (Takayama et al 1995(Takayama et al , 1997(Takayama et al and 1999. The IPV-motifs have been shown to be indispensable for binding to small heat shock proteins (sHSPs) (Fuchs et al 2010), the WW-domain binds LATS1 (Meriin et al 2018), and the PxxP domain is necessary for the interaction with dynein and PLC-γ (Doong et al 2000, Gamerdinger et al 2011).…”
Section: Introductionmentioning
confidence: 99%